2011
DOI: 10.1007/s10096-011-1155-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of nontuberculous mycobacteria isolates in elderly Taiwanese patients

Abstract: The aim of this study was to investigate the clinical significance of nontuberculous mycobacteria (NTM) isolates in elderly Taiwanese patients. From 2004 through 2008, patients >65 years old with NTM isolation were identified. The definitions of NTM disease followed the American Thoracic Society and Infectious Disease Society of America (ATS/IDSA) criteria. Among the 3,175 NTM isolates, Mycobacterium avium complex (MAC; n = 1,118, 35.2%) was the most prevalent species, followed by M. abscessus (n = 545, 17.2%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…8,20,21 In Taiwan, Lai et al reported an incidence rate of NTM disease of 2.23/100 000 outp atients 22 and 4.3/100 000 elderly patients (aged ⩾65 years), whereas their NTM colonisation rate was 15.8 in 2008. 23 Our results demonstrate a mean annual incidence of NTM disease of 1.9/100 000, in line with previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…8,20,21 In Taiwan, Lai et al reported an incidence rate of NTM disease of 2.23/100 000 outp atients 22 and 4.3/100 000 elderly patients (aged ⩾65 years), whereas their NTM colonisation rate was 15.8 in 2008. 23 Our results demonstrate a mean annual incidence of NTM disease of 1.9/100 000, in line with previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…The American Thoracic Society (ATS) and the Infectious Diseases Society of America (IDSA) have established guidelines to aid physicians in making the diagnosis of NTM. These guidelines indicate that in order to diagnose pulmonary NTM disease, clinical, radiological, and microbiological evidence of the disease should be met [5]. Table 3 shows criteria for diagnosing NTM according to ATS/IDSA guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows the most common NTM that cause infection in the elderly. They represent a diverse group of environmental organisms that can be isolated from water sources, soil, animals, and food [4, 5]. Human NTM infection is mainly acquired from environmental exposures [6, 7], although potential human-to-human transmission was recently suggested.…”
Section: Introductionmentioning
confidence: 99%
“…65 years of age from 2004 to 2008 and found that, of 1,339 patients with NTM isolates, 19.6% met ATS/IDSA criteria for disease. 24 MAC and M. abscessus were most common. Another single medical center report looked specifically at MAC in Taiwan and identified 22% as meeting ATS/IDSA diagnostic criteria.…”
Section: Asia-australiamentioning
confidence: 99%